A Ubiquitous Learning Model for Education and Training Processes Supported by TV Everywhere Platforms - Moreno-Lopez, Gustavo A.; Burgos, Daniel; Jimenez-Builes, Jovani A. (International Journal of Emerging Technologies in Learning, 2023)
Advances in technology and digital convergence, for example Netflix, enable users to view TV and video without time or place restrictions. These advances can be applied in education and training processes to enable ubiquitous learning (u-learning). However, a literature review (of the years 2002 to 2018) on u-learning models yielded scarce information about its implementation, specifically demonstrating a lack of application alternatives that could provide access to TV regardless of place and device. To contribute to this and other challenges in education, the objective of this study is to propose a reference model for u-learning implementation involving cloud-supported TV/video platforms. The model was validated in a university context by a group of experts and applied through a prototype in a real setting with students, and it showed favourable results and improvement in student performance.
Keywords: u-learning; multiscreen; model; TV everywhere; cloud computing; Emerging; Scopus